"Innovative Technologies, Problems and Their Solutions in Foreign Language Teaching" (Texas Journal of Multidisciplinary Studies, 2022)
Although modern teaching methods have been developed for teaching foreign languages, especially English as a foreign language, there are specific problems with learning. In this article we will consider these problems and the use of modern educational technologies